Drought Trends and Temperature Influence in Zhanghe River Basin, China - Bakhtawar Wagan; Zhanyu Zhang; Feng Baoping; Si Han; Amos T. Kabo-bah (Advances in Meteorology)
Our study area is one of the semiarid region of the China with under water stress condition that causes economic damage. The main objective of this study is to apply standardized precipitation evapotranspiration index (SPEI) and to use linear regression to calculate drought conditions in the study area. For this purpose, data from 1980 to 2010 was analyzed at different (1, 6, 12, and 24 months) time scales. Results depicted both dry and wet periods in the study area; occurrence of dry span with different frequency and magnitude was increased over last decades (2000–2010) at most of the stations. Statistical results demonstrated that temperature was decreased in the 1st decade in most of stations but in two decades from 1990 to 2000 and 2001 to 2010, temperature was increased except in Changzhi station. These results could be a future reference for developing information programs about monitoring and early drought information, planning of existing reservoirs, and management of water resources under climate conditions.